(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This study aims to identify human resources development and its role in the development of the insurance industry in the national insurance company, and to inspect how the recruitment requirements for human resource development and its impact in setting up efficient and skilled staff ,good, effective and well prepared based on scientific grounds. The concept has been identified the insurance industry as well as understanding human resources and its management and development the main requirements that lead to improve performance within the company. Divided into two main functions, the first type is the staff requirements and functions and the second kind is the requirements and functions of human resource development within the company. These requirements were analyzed and studied their impact on the development of the insurance industry in addition to the analysis of the characteristics of the sample. The study hypotheses were tested on a relationship and impact between the study variables through statistical methods related to the subject. The study concluded a set of conclusions and the most important are: • The human resources has an important and dynamic role in insurance companies so that companies could face competitive challenges by adopting strategic options in cost, technology and product type areas but could not continue to face challenges without human resources that do not have the knowledge and technical capabilities for the insurance process and enabling them to respond quickly to environmental changes. • The company discussed the benefits and improvement in work not only depends on its position in the insurance market and excess resources, but with the ability to invest the belonging human mind and tbe efficiently management and develop properly. Moreover, the most recommended by the study are: • The staff is considered as an important supplier resources owned by the company, the good and continuous work is a must for a better management, development and improvement to achieve company goals and improve their performance and increase their productivity. • Partial review by organizational structure of the Department of human resources management in the company and make all divisions and units of personnel linked to one central point which is: (human resources planning, performance assessment and motivate employees) or creating the kind of active communication mechanisms between these divisions in case of lack to review the current structure.